Kualitas Fisik Antimicrobial Edible Film (AmEF) dengan Ekstrak Daun Teh (Camellia sinensis) dari Gelatin Limbah Tulang Ayam - Windyasmara , Ludfia; Pertiwiningrum, Ambar; Erwanto, Yuny; Asmoro, Novian Wely; Afriyanti, Afriyanti (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2019)
This study intends to find out the impact of green tea leaves’ concentration and heating temperature on the physical quality of the antimicrobial edible film (AmEF) made from chicken bone gelatin. This study also utilizes chicken bone waste, in oder to increase both monetary value and the usefulness of that waste. The bone gelatin will then be utilized as AMeF and combined with green tea leaves’ extract (Camellia sinensis) that used as sausage wrapper. Several stages have been taken placed as follow: chicken bone gelatin production; green tea leaves extraction; and tea leaves’ extract-AMeF production. cCompletely randomized design with the factorial pattern was used in this study. Data was statistically analyzed using uni-variate analysis with 5% significance rate. Duncan’s Multiple Range Test (DMRT) will later be used to further test if there is a difference between each treatment. The physical qualities of AmEF that tested in this study include clarity, color, and thickness. The result of this study shows that a clarity value of AmEF was ranged between 0.62-2.12 abs, color was 0.87-2.60 abs, and 0.015-0.023 mm of thickness. The addition of tea extract and heating temperature have significant (P<0.05) effect on the clarity and color while have no effect on the thickness.